Conformational stabilization as a strategy to prevent nucleophosmin mislocalization in leukemia - María A. Urbaneja (Nature Portfolio, 2017)
Abstract Nucleophosmin (NPM) is a nucleolar protein involved in ribosome assembly and cell homeostasis. Mutations in the C-terminal domain of NPM that impair native folding and localization are associated with acute myeloid leukemia (AML). We have performed a high-throughput screening searching for compounds that stabilize the C-terminal domain. We identified three hit compounds which show the ability to increase the thermal stability of both the C-terminal domain as well as full-length NPM. The best hit also seemed to favor folding of an AML-like mutant. Computational pocket identification and molecular docking support a stabilization mechanism based on binding of the phenyl/benzene group of the compounds to a particular hydrophobic pocket and additional polar interactions with solvent-accessible residues. Since these results indicate a chaperoning potential of our candidate hits, we tested their effect on the subcellular localization of AML-like mutants. Two compounds partially alleviated the aggregation and restored nucleolar localization of misfolded mutants. The identified hits appear promising as pharmacological chaperones aimed at therapies for AML based on conformational stabilization of NPM.